Household food security and nutritional status of preschoolers in Valderrama, Antique - Braga, Mayet Ann.; Gordon, Cyrus John G.; Guisihan, Thanz Pamela G. (2005.)
This study is a cross-sectional survey of 138 randomly selected households from ten (10) similarly randomly-selected barangays in Valderrama, Antique. This study aimed to determine household food security and nutritional status of pre-schoolers in Valderrama, Antique.
Special Problem (Undergraduate, Bachelor of Science in Public Health)College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Food and nutrition -- Pre-school children -- Valderrama, Antique